Benin : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2003)
This paper reviews Benin's progress and proposes IMF Executive Board approval of the Completion Point Under the Enhanced Heavily Indebted Poor Countries (HIPC) Framework. The IMF staff and IDA consider that Benin has met the conditions for reaching the completion point under the enhanced HIPC Initiative, as specified in the decision point document. Benin's macroeconomic program is on track, as evidenced by satisfactory performance under the Poverty Reduction and Growth Facility (PRGF) arrangement, and the government has made considerable progress in implementing its structural adjustment program, albeit with delays.